The Determinants Stock Price Crash Risk of the Manufacturing Firms in Indonesia - Fidya Gumilang Arianwuri; Sutrisno T.; Yeney Widya Prihatiningtias (University of Merdeka Malang, 2017)
This study aimed to examine the effect of the business strategy of prospector and defender companies on stock price crash risk, test the influenced of equity market competition on stock price crash risk, and test the effect of prospector strategy on stock price crash risk through overvalued equities. The population of this study was manufacturing firms listed on the Indonesia Stock Exchange for seven years of observation. The data analysis used in this research was Path Analysis by using Multiple Linear Regression. The results of this study that the business strategy prospector positively affects the stock price crash risk, while the defender strategy did not affect the stock price crash risk. Companies that implemented business prospector strategies will be faced with higher uncertainty than defender business strategies. In addition, prospector's business strategy can affect the stock price crash risk through overvalued equities. Companies that implemented business prospector strategies will tend to overvalued equities, which can lead to future stock price crashes. One way reduced to the stock price crash risk is in the presence of equity market competition. The equity market competition had a negative effect on the stock price crash risk so that a high equity market competition can reduced information asymmetry and minimize the stock price crash risk.DOI: https://doi.org/10.26905/jkdp.v21i4.1353